Harmful Interference - Board, Editorial (Law, State and Telecommunications Review, 2019)
The article introduces this issue of the Law, State and Telecommunications Review by way of presenting its contents. Statutes, regulations, and judicial decisions of 2018 pertaining to telecommunications are referred to in detail. It also addresses the main political and juridical discussions on the Brazilian telecommunications sector that took place the year before the publication of the journal’s current volume.